Copper-catalyzed C–O coupling of styrenes with N-hydroxyphthalimide through dihydroxylamination reactions. Issue 45 (11th November 2015) - Xia, Xiao-Feng; Zhu, Su-Li; Zhang, Danting
Abstract: An efficient method of copper-catalyzed 1, 2-dihydroxylaminations of alkenes have been demonstrated under air conditions by using PhI(OAc)2 as oxidant to furnish the dioxygenated products in 20–81% yields. This provided an alternative methodology to synthesis of dioxygenated products, which were easily transformed into diols under the reductive conditions. Furthermore, a free-radical addition mechanism was proposed in this transformation. Graphical abstract: